A Case Report of Severe Coagulopathy in Antenatal COVID-19. (26th August 2022) - Sand, Anna; Chaireti, Roza; Sennström, Maria; Pettersson, Karin; Magnusson, Maria
Abstract : Pregnancy is a naturally occurring hypercoagulable state, and COVID-19 can cause profound changes in the coagulation system associated with thromboinflammation. We report a case of a pregnant woman with moderate symptoms of COVID-19 and a severe coagulopathy with unexpected low levels of fibrinogen and factor VIII as well as atypical thrombelastometry results. She developed a severe placental dysfunction with intrauterine fetal distress and perinatal death. The case did not fulfil the criteria for preeclampsia or sepsis, and the adverse outcome was assessed as a direct effect of the COVID-19 infection with placental insufficiency, despite absence of serious maternal pulmonary symptoms. Atypical persistent coagulopathy may serve as an important marker of a serious obstetrical situation in COVID-19.